Smart Control of Composition for Double Perovskite Electrocatalysts toward Enhanced Oxygen Evolution Reaction. Issue 23 (18th October 2019) - Sun, Hainan; Xu, Xiaomin; Chen, Gao; Zhou, Yupeng; Lin, Hong‐Ji; Chen, Chien‐Te; Ran, Ran; Zhou, Wei; Shao, Zongping
Abstract: Double perovskites have emerged as efficient candidates for catalyzing the electrochemical oxygen evolution reaction (OER). Smart control of the composition of a B‐site ordered double perovskite can lead to improved catalytic performance. By adopting a facile co‐doping strategy, the OER‐active elements are simultaneously introduced into the B‐site and B′‐site of a B‐site‐ordered double perovskite (A2 BB′O6 ), leading to an enhancement of the exposed reactive sites and an optimum surface chemical state. As a result, a model system built from the substitution of Co for Mo and Fe in the Sr2 FeMoO6− δ double perovskite (with a composition of Sr2 Fe0.8 Co0.2 Mo0.6 Co0.4 O6− δ ) shows significantly enhanced OER activity in alkaline media compared with the host material, requiring an overpotential of 345 mV to reach a 10 mA cm −2 current density (catalyst loading≈0.232 mgcat cm −2 GEO ) and a cell voltage of 1.57 V to afford the same current density for the overall water splitting when coupled with a Pt/C cathode (catalyst loading≈2 mg cm −2 ). It also demonstrates excellent electrochemical stability. The generalizability of the compositional control methodology has also been demonstrated in double perovskites incorporating transition metals other than Co (e.g., Ni). Abstract : Double the doping : Oxygen evolution reaction (OER)‐active elements are simultaneously introduced into the B‐site and B′‐site of a B‐site‐ordered double perovskite (A2 BB′O6 ), leading to an enhancement in the exposed reactive sites and an optimum surface chemical state. The A2 BB′O6 perovskite displayed remarkably long durability and excellent OER activity.